Arrestins contribute to amyloid beta-induced cell death via modulation of autophagy and the α7nAch receptor in SH-SY5Y cells - Liu, Yi-qing (Sci Rep, 2017)
Amyloid β-protein (Aβ) is believed to contribute to the development of Alzheimer’s disease (AD). Here we showed that Aβ(25-35) rapidly caused activation of autophagy, subsequently leading to reduction of autophagy associated with cellular apoptosis. Further investigation revealed that the accumulation of β-arrestin 1 (ARRB1) caused by Aβ(25-35) contributed to the induction of autophagic flux. The depletion of ARRB1 led to decreases in the expression of LC3B, Atg7, and Beclin-1, which are essential for the initiation of autophagy. ARRB1 depletion also reduced downstream ERK activity and promoted Aβ(25-35)-induced cell death. As with ARRB1, transient upregulation of ARRB2 by Aβ(25-35) was observed after short treatment durations, whereas genetic reduction of ARRB2 caused a marked increase in the expression of the α7nAch receptor at the cell surface, which resulted in partial reversal of Aβ(25-35)-induced cell death. Although expression of both ARRB1 and ARRB2 was reduced in serum from patients with AD, the levels of ARRB1 were much lower than those of ARRB2 in AD. Thus, our findings indicate that ARRB1/2 play different roles in Aβ(25-35) cytotoxicity, which may provide additional support for exploring the underlying molecular mechanism of AD.